2021
DOI: 10.1021/acs.jafc.1c04555
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hypertensive Peptide Predictor: A Machine Learning-Empowered Web Server for Prediction of Food-Derived Peptides with Potential Angiotensin-Converting Enzyme-I Inhibitory Activity

Abstract: Angiotensin converting enzyme-I (ACE-I) is a key therapeutic target of the renin−angiotensin−aldosterone system (RAAS), the central pathway of blood pressure regulation. Food-derived peptides with ACE-I inhibitory activities are receiving significant research attention. However, identification of ACE-I inhibitory peptides from different food proteins is a labor-intensive, lengthy, and expensive process. For successful identification of potential ACE-I inhibitory peptides from food sources, a machine learning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…33 Recently, Gazal Kalyan et al (2021) summarized the reported ACE inhibitory peptides and their IC 50 values. 34 Out of the 1648 ACE inhibitory peptides, only 117 peptides potently inhibited ACE with an IC 50 value below 3 μM, and about 43% peptides had an IC 50 lower than 60 μM. 34 The novelty and potency of the oligopeptides SpH-6 and SpH-7 revealed in this study demonstrated the efficiency by applying combined virtual screening and in vitro experimental investigation for the discovery of bioactive peptides from various dietary protein resources.…”
Section: Resultsmentioning
confidence: 82%
“…33 Recently, Gazal Kalyan et al (2021) summarized the reported ACE inhibitory peptides and their IC 50 values. 34 Out of the 1648 ACE inhibitory peptides, only 117 peptides potently inhibited ACE with an IC 50 value below 3 μM, and about 43% peptides had an IC 50 lower than 60 μM. 34 The novelty and potency of the oligopeptides SpH-6 and SpH-7 revealed in this study demonstrated the efficiency by applying combined virtual screening and in vitro experimental investigation for the discovery of bioactive peptides from various dietary protein resources.…”
Section: Resultsmentioning
confidence: 82%
“…Several factors contribute to the improved performance of MLACP 2.0, including (i) a reduced training dataset coupled with a meta -model approach; (ii) the predicted probabilistic features have a high intrinsic discriminatory ability on both datasets, resulting in improved performance. Interestingly, this approach can be extended to predict other peptide therapeutic functions [51] , [52] , [53] , [54] . Despite its promising performance, MLACP 2.0 also has room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“… 40 , 41 LOOCV was used to avoid overfitting and tune the hyperparameters because of our small data set size. 8 , 14 , 33 The hyperparameters with the best performance from LOOCV were used as the final model for performance evaluation with the test data set.…”
Section: Methodsmentioning
confidence: 99%